DAMPAK PANDEMI COVID-19 TERHADAP PERCERAIAN YANG DIAJUKAN OLEH PIHAK ISTERI DI INDONESIA - Judiasih, Sonny Dewi; Salim, Elycia Feronia (Faculty of Law, Parahyangan Catholic University, 2021)
The protracted pandemic caused by Covid-19 pandemic apparently, as observed in several regions in Indonesia, caused a significant increase in number of divorces initiated by women. In this paper, the author seeks to analyse this socio-legal phenomenon in comparison to similar situation occuring in other countries. Using a juridical-sociological and comparative law approach, the author seeks to identify what factors determines the decision to file a divorce and to what extent the Pandemi, significantly impacting macro economic as well as family economics influence the existing divorce rate.